Aven Green, baking machine - Bowling, Dusti (Bowling, Dusti. Aven Green., 2021)
"Aven knows she's an expert baker of cakes and cookies since she's been baking with her mom for a really long time. Plus no one bakes quite like she does. She cracks eggs with her feet and measures sugar and flour with her feet (plus measuring cups), since she was born without arms. And now Aven has her eye on the prize: a beautiful blue ribbon for baking at the county fair. So she teams up with her friends Kayla, Emily, and Sujata. But it turns out they all have very different tastes and a lot of opinions about baking. Talk about a recipe for disaster!"--